A functional polymorphism in the interleukin-1beta and severity of nicotine dependence in male schizophrenia: A case-control study. (May 2015) - Zhang, Xiang Yang; Chen, Da-Chun; Tan, Yun-Long; Tan, Shu-ping; Luo, Xingguang; Zuo, Lingjun; Rao, Wenwang; Yu, Qiong; Kou, Changgui; Allen, Melissa; Correll, Christoph U.; Wu, Jingqin; et al.
Abstract: Previous studies have shown that the functional 511C/T polymorphism in the IL-1beta-gene may be implicated in the susceptibility for schizophrenia. Moreover, recent studies suggested that IL-1 participates in the progression of lung disease in smokers, which are overrepresented in schizophrenia. We aimed to investigate the possible relationship between the IL-1beta-511 C/T polymorphism and smoking behavior in schizophrenia versus healthy controls in a Chinese population. The IL-1beta-511C/T polymorphism was genotyped in 638 male patients with chronic schizophrenia (smoker/never-smoker = 486/152) and 469 male controls (smoker/never-smoker = 243/226). The cigarettes smoked per day, the Heaviness of Smoking Index (HSI) and the Fagerstrom Test for nicotine dependence (FTND) were assessed. Patients were also rated on the Positive and Negative Syndrome Scale (PANSS). The results showed no significant differences in genotype and allele distribution between patients and controls, and between smokers and never-smokers in either the patient or control group. However, in patients, smokers with the C/C genotype had significantly higher HSI (p < 0.005) and FTND (p < 0.05) scores than smokers with the T/T genotype, without significant differences in controls. Furthermore, there was a linear positive correlation between the number of C alleles and the HSI (p < 0.005) in patients. Our findings suggest that the IL-1beta-511 C/T polymorphism may not be related to schizophrenia or smoking status in Chinese individuals, but may affect the severity of nicotine dependence among male smokers with schizophrenia. Highlights: To examine the association of IL-1 beta with smoking in schizophrenia. The IL-1beta-511C/T polymorphism was genotyped in male patients and controls. This polymorphism was associated with nicotine dependence in schizophrenia smoker.